The Impact of Grammar, Vocabulary, and Reading Interest on Descriptive Writing Skills in Islamic Higher Education - Nurul Hidayati; Luthfatul Qibtiyah; Uswatun Hasanah (Lembaga Pengembangan Kinerja Dosen, 2025)
Reading interest, grammar mastery, and vocabulary knowledge are crucial components that contribute to students’ ability to produce effective descriptive texts. This study aims to analyze the influence of these three variables on students’ descriptive writing ability at the university level. The research was conducted at the University of Al-Amien Prenduan, involving first- to third-semester students from the Islamic Economics Study Program and other related programs under the Faculty of Islamic Economics and Business. A purposive sampling technique was used to select 109 students who had completed at least one semester of English instruction. Employing a quantitative approach with a correlational design, this study utilized a closed-ended questionnaire to measure grammar mastery, vocabulary knowledge, and reading interest, as well as a descriptive writing test to assess students’ writing ability. Multiple linear regressions were applied to analyze the simultaneous and partial effects of the independent variables. Results revealed that grammar mastery, vocabulary knowledge, and reading interest jointly influenced students’ descriptive writing ability significantly. Individually, grammar mastery and vocabulary knowledge showed statistically significant positive effects, while reading interest had a positive but non-significant impact. These findings highlight the importance of grammatical and lexical competence in academic writing, while also indicating the need for more innovative and practical strategies to foster reading interest..